The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.14309/crj.0000000000000003
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Severe, Nilotinib-Induced Liver Injury

Abstract: Idiosyncratic hepatotoxicity is a leading reason for the discontinuation or dose modification of Food and Drug Administration (FDA)-approved medications in the United States. We report the case of a 53-year-old woman with chronic myeloid leukemia who developed acute cholestatic hepatitis in response to the tyrosine kinase inhibitor nilotinib. Nilotinib was discontinued, and the patient's liver function tests normalized over the next 3 months. We conclude that nilotinib may cause life-threatening hepatotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In comparison, only two of the five UGT1A1 NMs experienced high-grade toxicities [ 82 ]. Single patient case reports have described similar findings of severe nilotinib-induced hyperbilirubinemia among UGT1A1 PMs [ 83 , 84 , 85 , 86 ]. Some of the studies identified in our review proposed that UGT1A1 results may help avoid treatment delays and adverse events, but there is a lack of implementation studies assessing UGT1A1 -guided nilotinib prescribing.…”
Section: Resultsmentioning
confidence: 75%
“…In comparison, only two of the five UGT1A1 NMs experienced high-grade toxicities [ 82 ]. Single patient case reports have described similar findings of severe nilotinib-induced hyperbilirubinemia among UGT1A1 PMs [ 83 , 84 , 85 , 86 ]. Some of the studies identified in our review proposed that UGT1A1 results may help avoid treatment delays and adverse events, but there is a lack of implementation studies assessing UGT1A1 -guided nilotinib prescribing.…”
Section: Resultsmentioning
confidence: 75%
“…Severe liver injury was also reported in patients with CML treated with nilotinib and dasatinib. 10 , 11 However, among several studies comparing imatinib with the other BCR-ABL TKIs, 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 only one mentions hepatic effects without stratification study. 19 Hence, it is necessary to perform a meta-analysis focusing specifically on the relative risk of hepatotoxicity associated with each BCR-ABL TKI.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of grade 3 or 4 elevation of liver enzymes caused by nilotinib was reported 1 to 4% (2). Belopolsky et al reported a case of the patient with nilotinib-induced grade 4 hepatotoxicity, which was normalized after the cessation of nilotinib (3). In that report, the liver biopsy showed acute hepatitis with severe portal and lobular inflammation, although the exact types of infiltrating immune cells or their activation status were not studied (3).…”
Section: Discussionmentioning
confidence: 98%
“…Belopolsky et al reported a case of the patient with nilotinib-induced grade 4 hepatotoxicity, which was normalized after the cessation of nilotinib (3). In that report, the liver biopsy showed acute hepatitis with severe portal and lobular inflammation, although the exact types of infiltrating immune cells or their activation status were not studied (3). There have also been several case reports of imatinib-induced liver injury, which did not identify the actual "killer cells" in the liver.…”
Section: Discussionmentioning
confidence: 99%